KNOWLEDGE AND AWARENESS OF STD AND AIDS AMONG ADOLESCENT GIRLS IN URBAN SLUMS OF RAIPUR CITY .(C.G.) - Dr RASHMIGOUR PATEL, (International Journal of Pharma and Bio Sciences, 2016)
Title:-Knowledge and Awareness of STDs and AIDS among adolescent girls in urban slums of Raipur city.Background:-Sexually transmitted diseases and AIDs are very important health challenges for adolescents. Many national and international governmental and nongovernmental health agencies are running programmes to reduce the incidence of these. We can povide an insight to the reproductive and exual health needs of adolescents by assessing their knowledge, attitude and practice about these diseases.Objectives-.To assess knowledge, awareness and practice regarding STDs and AIDs. Methodology:-Study design-Cross sectional study done in the year 2004. Sample size-4000 adolescent girls’ .Inclusion criteria- Girls of age group 10 to 19 years residing in urban slums. Sampling method- Cluster sampling method to choose clusters of 40 slums from list of 215 slums in Raipur city, 100Subjects selected by house to house survey from each slum. Material- Predesigned and pretested questionnaireAnalysis-Proportion analysis using standard SPSS and chi square test. Results: - Knowledge about STDs and AIDs was present in 43.6 % of respondents.